(untitled) (The Research of Medical Science Review, 2025)
Objective: To compare the mean serum total bilirubin levels following the administration of vitamin D plus phototherapy versus phototherapy alone in neonates with jaundice. Study Design: Randomized Controlled Trial. Study Setting: Akhtar Saeed Trust Hospital, Lahore Study Period: November 2023 to April 2024. Methods: A total of 60 neonates meeting the inclusion criteria were randomized into two groups. Group A received phototherapy and 1000 IU of vitamin D daily for five days, while Group B received phototherapy alone for up to seven days. Serum bilirubin levels were measured at admission and after treatment. Data were analyzed using SPSS version 20, with an independent sample t-test used to compare groups. Statistical significance was set at p < 0.05. Results: Baseline bilirubin levels were comparable between groups. Post-treatment, Group A had significantly lower mean bilirubin levels (7.15 ± 0.37 mg/dL) compared to Group B (8.23 ± 0.39 mg/dL, p < 0.001). This reduction was consistent across all demographic and clinical variables. Conclusion: The addition of vitamin D to phototherapy significantly enhanced bilirubin reduction in neonatal jaundice, supporting its use as an adjuvant therapy to improve treatment outcomes